Community Perception and Indigenous Adaptive Response to Climate Variability at Tehuledere Woreda, South Wollo - Seid, Mohammed (Engineering International, 2013)
Climate variability and extreme events have wide range economic, social and environmental impacts. In adaptation of these impacts, it is very important to assess and change the perception and awareness level of local community to climate variability and adaptation responses. Assessing the indigenous adaptation mechanisms and adaptation capacity is the integral part in addressing the adverse consequences of climate variability. There was no study, which assessed the adaptation to climate variability with integrating community perception in the study area. Thus, this study was aimed to fill this gap. The study has shown that, majority of participants were observed the existence of climate variability and indicators, But significant number of participants failed to perceive the causes of the variability. The effects of climate variability in the study area are land degradation, deforestation, decline of crop production, death of livestock, loss of grazing land, and destruction of infrastructures. The local communities have own adaptation methods, which include, production of different crops, planting of special variety crops, using of natural and chemical fertilizers, irrigation farming, planting of trees, and soil conservation. Adjusting the production season with the variability of climate is other cope up mechanism of farmers. The participants had problems with materials, financial and training supports from NGOs and governments.